The effects of mental stress on swimmers` performance and psychophysiological variables - Welp, U. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Chronic stress is defined as a state of threatened homeostasis in which affective, physiological, biochemical and cognitive changes could lead to many diseases. Yet, acute stress represents the body`s reaction to a current situation and can be specifically negative during an activity that requires working memory and decision-making. Following that, some studies demonstrate cognitive exertion (e.g., arithmetic tasks) has a negative effect on subsequent physical performances [1] possibly by the modulation of the autonomic nervous system [2] and others psychophysiological variables [3]. We hypothesized that a mental stress task would be associated with lower performance in a swimming test. Moreover, the perceived exertion would increase as the focus becomes more associative and the affect gets negative. METHODS: Five randomized competitive swimmers (15±0,44y) participated in a mental stress (ME) and control condition (CON) before a swimming test. In ME, athletes performed continuous arithmetic tasks for 15 min. In CON, they sat quietly with eyes opened for 15 min. A 200 m maximal swimming test analysis was performed and stroke length, stroke rate, and stroke index from each split were individually analyzed. Ratings of perceived exertion, heart rate variability, attentional focus, and affect (arousal and valence) were collected before the warm-up (M1), after the warm-up (M2), after ME or CON (M3), after the swimming test (M4) and 20 min after the test (M5). A two-way ANOVA was used to determine the effects of condition (ME and CON) and time (M1, M2, M3, M4) for all dependent variables. A t-test was used to compare the 200 m time from both conditions. RESULTS: There was a significant condition x time interaction for arousal (p=0.02) and a main effect for time (p<0.05), but not for condition (p=0.38). There was no significant condition x time interaction for affective valence, attentional focus, or perceived effort (p>0.05). However, there was a main effect for time for focus (p=0.04) and perceived effort (p<0.05). Besides, there was no significant condition x time interaction for 50 m splits times, HF and LF/HF ratio (p>0.05) or main effect for condition (p>0.05), but there was a main effect for time for 50 m splits time (p=0.01). There was a significant interaction between condition x time for LF (p<0.05), but no main effect for condition or time for LF (p>0.05). In addition, the t-test revealed significant interactions between both conditions (p<0.05). CONCLUSION: As hypothesized, athletes decreased performance when swimming after a mental stress task. Besides exercise, mental stress pre-exercise also modulated athlete`s responses by increasing arousal, perceived exertion, and sympathetic activity, also focus became more associative. Therefore, the athletes were 1,842 s slower in the ME. For future reference, it would be interesting to investigate whether coping strategies can interact with these results.